Automatic Yaw Rotation of Plates on Roller Tables. Issue 11 (2021) - Waldmann, Andreas; Kugi, Andreas; Steinboeck, Andreas
Abstract: Yaw rotations of plates are frequently required in heavy-plate rolling between roll passes in longitudinal and lateral plate direction. The primary objective are fast and accurate plate rotations to ensure a high throughput. This paper deals with automatic 90 ◦ yaw rotations of plates on a roller table with shouldered rolls spinning in opposite direction. A two-degrees-of-freedom control strategy is derived based on a mathematical model. The model also captures the friction forces between the roller table and the plate, which are essentially required for the rotation. Unknown parameters of the model are identified based on measurements from an industrial plant. Such measurements also serve for model validation. An infrared camera is used to track the current position of the plate on the roller table. Based on these measurements, a state observer estimates non-measurable process variables. Finally, the estimator and control design is tested in simulations based on the validated model.